Performance study of fractional frequency reuse in ofdma network / Mohamad Hussain F Snosi - Mohamad Hussain , F Snosi (2017)
Long Term Evolution (LTE) technology is considered as the most possible candidate for recent generation mobile communications. LTE networks offer high capacity and are specified and designed to accommodate small, high performance, power-efficient end-user devices. One limiting factor that influences LTE performance is the interference from neighbor cells, the so called Inter-Cell Interference (ICI). Fractional Frequency Reuse (FFR) has been proposed as a technique to overcome this problem, since it can efficiently utilize the available frequency spectrum. This project analyzes the FFR scheme which dynamically selects the optimal frequency allocation based on the cell total throughput and user satisfaction. In detail, the mechanism divides the cell into inner and outer regions and then selects the optimal size as well as the optimal frequency allocation between these two regions with main target to maximize the overall throughput and user satisfaction. The mechanism is evaluated through several simulation scenarios that incorporate users’ mobility. With the use of MATLAB simulation, which is highly configurable, this project will study a performance of frequency reuse technique in OFDMA. Simulation results show that the adaptation process leads to improved performance and increased total cell throughput and user satisfaction.